2007
DOI: 10.1080/01926230701347330
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity Evaluation: Comparison of Tumor Data from Dual Control Groups in the CD–1 Mouse

Abstract: Current regulatory thinking allows for the use of single control groups for rodent carcinogenicity testing although there has been a trend until recently to use dual control groups. To date, virtually nothing has been published on whether a shift from dual to single control groups will affect the identification of tumorigenic risk potential in these studies. A recent evaluation of dual control carcinogenicity data in the rat (Baldrick, Toxicol Pathol 2005, 33: 283-291) showed that although no major differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…There are very few reports of this kind in the literature (Maita et al 1988;Frith et al 1996Frith et al , 2001Son and Gopinath 2004;Baldrick and Reeve 2007;Giknis and Clifford 2010), with the majority of reports being those of C57BL6 and B6C3F1 mice (Tamano et al 1988;Ward et al 1999). The findings in this study were generally consistent with the occurrence of similar lesions described in other mouse strains.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few reports of this kind in the literature (Maita et al 1988;Frith et al 1996Frith et al , 2001Son and Gopinath 2004;Baldrick and Reeve 2007;Giknis and Clifford 2010), with the majority of reports being those of C57BL6 and B6C3F1 mice (Tamano et al 1988;Ward et al 1999). The findings in this study were generally consistent with the occurrence of similar lesions described in other mouse strains.…”
Section: Discussionmentioning
confidence: 99%
“…Dual control groups can be and have been used to assess intrinsic variability in groups of animals on study. For example, a review of dual control groups in CD-1 mice highlighted the wide variability in tumor incidence rates within a study (Baldrick and Reeve 2007). In one study, the lymphoma incidence was 3/60 in control group I and 11/59 in control group II.…”
Section: Innate Biological Variabilitymentioning
confidence: 99%
“…Consistent diagnostic criteria were applied in the interpretation of these findings. Some authors did publish the diagnostic criteria used in their studies but reported that the criteria changed for studies included in the published historical data (Baldrick and Reeve 2007;McMartin et al 1992;Tennekes et al 2004aTennekes et al , 2004b. Other authors have compiled HCD tables where the same pathologists were involved in all aspects of the evaluation and peer review process, to ensure consistency between the studies used in the tabulation of data (Brix et al 2005).…”
Section: Tissue Sampling and Trimming Proceduresmentioning
confidence: 99%
“…Histiocytic sarcomas of the epididymis have been described by Baldrick and Reeve (2007); Itagaki, Tanaka, and Shinomiya (1993); Shiga (1994);and Yano et al (2008).…”
Section: Adenoma Leydig Cellmentioning
confidence: 99%